A transportation and location optimization model: minimizing total cost of oilseed crushing facilities in Kansas - Luna Meiners, Shauna Nicole (Kansas State University, 2016)
Markets for alternative fuels are emerging and are of great interest to both public and private companies, as well as government agencies looking to differentiate fuel sources to achieve improved and sustainable operational efficiencies. This creates a growing need for innovation and an increased supply of biofuel feedstocks for bioenergy options such as bio-jet fuel. This thesis aims to assess the logistical feasibility of producing oilseed bio feedstocks and the practicality of building new crush facilities specifically for bio-jet fuel production in Kansas. A logistical optimization model is built by applying data to estimate the potential Kansas supply of rapeseed as a possible feedstock option; transportation and facility costs associated with building; and proposed crushing facility sites, by considering the estimated demand for bio-jet fuel within Kansas. The developed optimization model determined that even average yields per acre and modest adoption rates by farmers willing to incorporate rapeseed into their crop rotations could provide enough feedstock to supply one or two crushing facilities, depending on a variety of additional factors, including bio-jet fuel demand in Kansas. Sensitivity analysis was performed on key model factors and determined that the most influential factor on both size and number of proposed crushing facilities was the market demand for bio-jet fuel. Ultimately, further research is required to better understand the actual market demand for bio-jet fuel within Kansas and how competition or supply supplementation of other bio feedstocks can affect the size or number of proposed crushing facilities. There are currently six oilseed crushing facilities operating in Kansas; although all are dedicated to soybean or sunflower seed. Further studies may find these sites as viable alternative options to building new crushing facilities for a separate type of feedstock.
Keywords: Feedstock; Biofuel; Bioenergy; Commercial Airlines; Optimization; Logistics